Flipped Classroom 2.0: Producing and Synthesising the Knowledge - Aras Bozkurt; Hasan Uçar (Anı Publishing, 2018)
The flipped classroom model is a new method in education by reversing the usual learning and teaching processes. The main purpose of this study is to reveal the opinions and perceptions of the students about the flipped classroom model. The research was conducted in a course designed as blended learning, which was followed both face to face and online. A case study design was used in this qualitative research. The research group of the study consisted of 35 undergraduate students who took a course designed with the flipped classroom model in the 2017-2018 academic year. The data were collected through online semi-structured open-ended questions. The data were analyzed through content analysis. As a result of the analysis, five themes related to the flipped classroom model emerged. The themes are active learning, cognitive readiness, reinforcement, course preparation, fun learning, and permanent learning. The findings of this promising method of learning are similar to the findings in the literature. Within this context, it is recommended to use the flipped classroom 2.0 model in teaching processes.